An Analysis of Anomalous Exchange in Young Learners’ Classroom Interaction - Rahma Sakina (Biormatika : Jurnal ilmiah fakultas keguruan dan ilmu pendidikan, 2020)
This research aims to analyze the classroom interaction in teaching learning process and the categories of anomalous exchanges that occur during classroom interaction in a fifth grade of an elementary school. The research employed a case study as a research methodology. Document analysis was used as data collection technique of this research. The documents analyzed were videos of teaching learning process in an elementary school in Bandung. The findings showed that the classroom interaction was dominated by Teacher Talk in which the teacher delivered information mostly through question and answer activities. Unanswered questions by the learners and no feedback from the teacher contributed to the occurrence of anomalous exchanges. In terms of anomalous exchanges, the findings revealed that defective exchanges and elliptical exchanges mostly occurred during the classroom interaction. Several factors which influenced the occurrence of these exchanges were the topic discussed, the wait-time, the types of teacher’s questions, and the non-conducive of learners’ situation.